2004
DOI: 10.1128/jcm.42.3.1024-1029.2004
|View full text |Cite
|
Sign up to set email alerts
|

Human β-Defensins 2 and 3 Demonstrate Strain-Selective Activity against Oral Microorganisms

Abstract: Human ␤-defensins 2 and 3 (HBD-2 and HBD-3) are inducible peptides present at sites of infection in the oral cavity. A few studies have reported broad-spectrum antimicrobial activity for both peptides. However, no comprehensive study has thoroughly investigated their potential against oral pathogens. The purpose of this study was to test the effectiveness of HBD-2 and HBD-3 against a collection of oral organisms (Actinobacillus actinomycetemcomitans, Fusobacterium nucleatum, Porphyromonas gingivalis, Peptostre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
251
6
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(278 citation statements)
references
References 43 publications
(47 reference statements)
17
251
6
1
Order By: Relevance
“…Although there are available animal models and a potent hBD-2 ready to test this potentially applicable clinical treatment modality, several questions need to be addressed before a workable animal study model may be established. We stepwise tested the antimicrobial activity against C. albicans 613p that was to be used as part of the study model and verified its sensitivity to hBD-2, which has been shown to be a potent antimicrobial agent against some strains of C. albicans [6,32,33]. The effective concentrations of hBD-2 against C. albicans are 1-14 μM based on published reports, which coincides with our finding using C. albicans 613p.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Although there are available animal models and a potent hBD-2 ready to test this potentially applicable clinical treatment modality, several questions need to be addressed before a workable animal study model may be established. We stepwise tested the antimicrobial activity against C. albicans 613p that was to be used as part of the study model and verified its sensitivity to hBD-2, which has been shown to be a potent antimicrobial agent against some strains of C. albicans [6,32,33]. The effective concentrations of hBD-2 against C. albicans are 1-14 μM based on published reports, which coincides with our finding using C. albicans 613p.…”
Section: Discussionsupporting
confidence: 76%
“…1A) are in accordance with a report by Liu et al [6], which showed that E. coli is only sensitive to hBD-2 under low salt conditions. Porphyromonas gingivalis ATCC 33277 was also sensitive to hBD-2 but at a higher concentration, as reported by Joly et al [32], although it was more resistant than E. coli. Under low salt conditions, growth of P. gingivalis at 10 μM hBD-2 was completely inhibited (Fig.…”
Section: Antifungal Activities Of Hbd-2 Against C Albicans and P Gisupporting
confidence: 64%
See 1 more Smart Citation
“…As mentioned earlier, although HBD-2 has shown antimicrobial effect on many oral and periodontal bacteria, those that play a critical role in periodontal diseases are relatively resistant to HBD-2 or require a very high concentration of HBD-2 to be killed, such as certain strains of A. actinomycetemcomitans, F. nucleatum, and P. gingivalis (MICs ranged from 6.5 to >250 µg/ml HBD-2) [64]. Sawaki et al [37] measured the HBD-2 concentration in normal oral epithelium to be ~40 µg/ml and as high as ~3.85 mg/ml in the oral squamous cell carcinoma samples.…”
Section: Discussionmentioning
confidence: 99%
“…These peptides also show strain-specific activity toward various Candida spp. (Joly et al, 2004). Interestingly, Wu and coworkers showed that hBD-3 activity against E. coli was unaffected by disulfide bonding which was previously thought to be critical to antimicrobial function .…”
mentioning
confidence: 99%